2008
DOI: 10.1007/s00125-008-1026-8
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide activates translation in rat pancreatic beta cells through calcium-dependent mTOR, PKA and MEK signalling pathways

Abstract: Aims/hypothesis Prolonged exposure of rat beta cells to the insulin secretagogue glibenclamide has been found to induce a sustained increase in basal insulin synthesis. This effect was calcium-dependent and localised in cells that had been degranulated by the drug. Since it was blocked by the translation inhibitor cycloheximide, we examined whether sustained exposure to glibenclamide activates translational factors by calcium-dependent signalling pathways. Methods Purified rat beta cells were cultured with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In islet beta cells during glibenclamide stimulation, Ca 2? activates mTOR via PKA/PKBdependent and -independent pathways [51]. In PC-12 cells, hypoxia-stimulated influx of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In islet beta cells during glibenclamide stimulation, Ca 2? activates mTOR via PKA/PKBdependent and -independent pathways [51]. In PC-12 cells, hypoxia-stimulated influx of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…is an important regulator of mTOR activation in various types of cells [26,30,51]. In primary mouse Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that glibenclamide, a second-generation sulfonylurea drug, also exerts stimulatory effects on b-cell protein and insulin synthesis when present over a prolonged period both in vivo and in vitro (Ling et al 2006). This chronic effect was achieved through an activation of translation at the steps of initiation and elongation, as evidenced by phosphorylation of the eukaryotic initiation factor 4E-binding protein 1 (4E-BP1) and of ribosomal protein S6 (rpS6), and dephosphorylation of eIF2a and of eukaryotic elongation factor 2 (eEF2; Wang et al 2008). It was shown to be calcium dependent and mediated through the mammalian target of rapamycin (mTOR; also known as mechanistic target of rapamycin, MTOR), protein kinase A (PKA), and MAPK/ERK kinases (MEKs; Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This chronic effect was achieved through an activation of translation at the steps of initiation and elongation, as evidenced by phosphorylation of the eukaryotic initiation factor 4E-binding protein 1 (4E-BP1) and of ribosomal protein S6 (rpS6), and dephosphorylation of eIF2a and of eukaryotic elongation factor 2 (eEF2; Wang et al 2008). It was shown to be calcium dependent and mediated through the mammalian target of rapamycin (mTOR; also known as mechanistic target of rapamycin, MTOR), protein kinase A (PKA), and MAPK/ERK kinases (MEKs; Wang et al 2008). Thus, glibenclamide, which is used for its acute stimulatory effect on insulin release, exerts an mTOR-dependent stimulation of insulin synthesis when present for prolonged periods .…”
Section: Introductionmentioning
confidence: 99%